Delivering integrated hypertension care at private health facilities in urban Pakistan: a process evaluation - Muhammad Amir Khan (BJGP Open, 2018)
Background: In Pakistan about 18% of all adults are affected by hypertension, and only one in eight of the prevalent cases have their hypertension controlled. As in many other low-middle income countries, a public–private partnership approach is being considered for delivering non-communicable disease care in urban areas. Aim: This process evaluation was undertaken to understand how an integrated care intervention was experienced by the care providers and patients, and to inform modifications before possible scaling. Design & setting: The mixed-methods study was conducted as part of a cluster randomised trial on integrated hypertension care at 26 private clinics. Method: The care practices were assessed by analysing the clinical records of 1138 registered patients with hypertension. Then semi-structured interviews with service providers and patients were used to understand their respective care experiences. A framework approach was applied to analyse and interpret the qualitative data. Results: District-led objective selection and context-sensitive staff training helped to get the clinics engaged in partnership working. About one-third of patients with hypertension had associated diabetes or renal compromise. The prescription of drugs is influenced by multiple non-clinical considerations of providers and patients. Many doctors allowed the use of home-based remedies as supplements to the prescribed allopathic drugs. Female patients faced more challenges in managing lifestyle changes. The intervention improved adherence to follow-up visits, but patient attrition remained a challenge. Conclusion: The integrated hypertension care intervention at private clinics is feasible, and leads to improved diagnosis and treatment in low-income country urban setting. The authors recommend continued implementation research and informed scaling of hypertension care at private clinics.